2012
DOI: 10.1007/s00405-012-2231-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in rat intrinsic laryngeal muscles: analysis of muscle fibers, muscle fiber proteins, and subneural apparatuses

Abstract: We compared age-related changes in the intrinsic laryngeal muscles of aged and young adult rats by determining the number and diameter of muscle fibers, contractile muscle protein (myosin heavy chain isoforms, MHC) composition, and the morphology of the subneural apparatuses. In aged rats, both the numbers and the diameters of muscle fibers decreased in the cricothyroid (CT) muscle. The number of fibers, but not diameter, decreased in the thyroarytenoid (TA) muscle. In the posterior cricoarytenoid (PCA) muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
3
19
1
Order By: Relevance
“…Biochemical alterations in TA muscle composition have structural, physiological, and functional implications, as demonstrated in this and previous studies using an aging rat model. Age‐related changes in TA muscle structure are evidenced by an overall reduction in the number of TA muscle fibers, muscle fiber atrophy, and an increase in the abundance of intramuscular connective and adipose tissues . The reduction in the proportion of fast contracting isoforms, specifically a reduction in the superfast MHCIIL isoform, that we observed in the present study is consistent with previously reported findings, and may indicate the transformation or replacement to a slower contracting muscle fiber type .…”
Section: Discussionsupporting
confidence: 91%
“…Biochemical alterations in TA muscle composition have structural, physiological, and functional implications, as demonstrated in this and previous studies using an aging rat model. Age‐related changes in TA muscle structure are evidenced by an overall reduction in the number of TA muscle fibers, muscle fiber atrophy, and an increase in the abundance of intramuscular connective and adipose tissues . The reduction in the proportion of fast contracting isoforms, specifically a reduction in the superfast MHCIIL isoform, that we observed in the present study is consistent with previously reported findings, and may indicate the transformation or replacement to a slower contracting muscle fiber type .…”
Section: Discussionsupporting
confidence: 91%
“…Previous literature suggests that the number of muscle fibers decreases in the TA. Depending on which fibers are more susceptible to denervation, this may reveal differences between male and female rat TA muscles in old age . Fiber type composition warrants further study in an aged rat model to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study, Nishida et al compared the behavior of laryngeal intrinsic muscles (CT = cricothyroid muscle; TA = thyroarytenoid muscle; PCA = posterior cricoarytenoid muscle) in adult and aged Wistar rats, analyzing the measurement of muscle fiber number and diameter (stained with hematoxylin‐eosin and observed using light microscope), muscle contractile protein composition through analysis of the composition of myosin heavy chain isoforms (using gel electrophoresis method), and quantitative analysis of subneural apparatuses (using scanning electron microscopy [SEM]). In the elderly rats, the authors found a significant decrease in the diameter and number of CT muscle fibers, as well as a decrease in the number but not the diameter of the TA.…”
Section: Discussionmentioning
confidence: 99%